2019
DOI: 10.7202/1071139ar
|View full text |Cite
|
Sign up to set email alerts
|

On Epistemic Responsibility While Remembering the Past: The Case of Individual and Historical Memories

Abstract: Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne. https://apropos.erudit.org/fr/usagers/politique-dutilisation/ Cet article est diffusé et préservé par Érudit.Érudit est un consortium interuniversitaire sans but lucratif composé de l'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(28 reference statements)
0
3
0
1
Order By: Relevance
“…It has been suggested that individuals can adopt a range of viewpoints, both internal and external, visual and non-visual, that can blend or integrate in different ways when recalling the past ( McCarroll and Sutton, 2017 ; McCarroll, 2018 ). In fact, incorporating multiple affective and evaluative perspectives, including those of others involved in the past event, may provide the most comprehensive understanding of the past experience ( Habermas, 2019 ; Trakas, 2019b ). Further empirical research is nevertheless necessary to fully explore these possibilities.…”
Section: The Traveler and The Past Selfmentioning
confidence: 99%
“…It has been suggested that individuals can adopt a range of viewpoints, both internal and external, visual and non-visual, that can blend or integrate in different ways when recalling the past ( McCarroll and Sutton, 2017 ; McCarroll, 2018 ). In fact, incorporating multiple affective and evaluative perspectives, including those of others involved in the past event, may provide the most comprehensive understanding of the past experience ( Habermas, 2019 ; Trakas, 2019b ). Further empirical research is nevertheless necessary to fully explore these possibilities.…”
Section: The Traveler and The Past Selfmentioning
confidence: 99%
“…This effect occurs, for example, when eyewitnesses to a crime form false beliefs about an event that they have witnessed because their recollection of the event is updated to reflect false information provided to them by others (e.g other eyewitnesses, suggestive police questioning) after the event (Loftus 2005). Reconsolidation provides the opportunity for false information to influence how an event is remembered but it can also bring epistemic benefits, allowing people to form more accurate representations of the past if the information that updates the memory is accurate and the initial memory is partial, blurred, or includes elements of inaccuracy (Puddifoot and Bortolotti 2019;Trakas, 2019). However, traumatic memories seem not to be as malleable as (at least some) other memories (Ehlers, Hackmann, & Michael, 2004).…”
Section: The Epistemic Harms Of Fear Generalisationmentioning
confidence: 99%
“…Por último, otro aspecto totalmente omitido es la perspectiva de segunda persona (Pérez y Gomila, en prensa), es decir, la perspectiva afectiva de otro partícipe del evento recordado. La perspectiva afectiva de un evento pasado puede ser construida en algunos casos de manera dialógica, a través de la interacción real entre los involucrados en el evento recordado (Harris et al, 2011), como por ejemplo cuando una pareja recuerda un pasado común (Trakas, 2019). Pero también la perspectiva de segunda persona puede ser internalizada por el sujeto, el cual, en el proceso de (re)evaluación del evento recordado, puede alternar entre su propia perspectiva y la perspectiva imaginada o recordada del otro involucrado en el evento.…”
Section: Marco General De Análisis De Los Recuerdos Personales Como Recuerdos Afectivosunclassified